Space time variation of lightning activity over northeast India - M.I.R. Tinmaker; K. Ali (Meteorologische Zeitschrift, 2012)
This paper presents a study of space-time variation of flash rate density over Northeast India (NEI) by using monthly satellite-based lightning flash grid (0.5° x 0.5° : 55 km x 55 km) data for a period of 10 year (1998-2007). The data are examined in terms of spatial, annual and seasonal distribution of the flash rate density. It is found that lightning flash rate density is maximum (55 flkm2 yr1) over the west of northeast India. This high flash rate density is attributed to the topography and the geography of NEI along with the moisture availability over the region. The inter-seasonal comparison of the flash rate density shows that the occurrence of the highest flash rate density during pre-monsoon is due to convective instability giving rise to Nor'westers. Orography of the region and the availability of the moisture control the development of thunderstorm during monsoon season. Shifting of the maximum lightning activity longitudinally during post-monsoon is attributed to the northeast monsoon activity. Development of front-like situation in the low altitude western region of the NEI, due to interaction of dry and cold air from higher latitudes with the warm and moist air caused by Western disturbances, trigger the thunderstorm development process over the region during winter season. The annual variation of flash rate density over the NEI exhibits two peaks- one prominent peak in April and the other smaller peak in September. The first peak is associated with intense insolation, extension of moisture content to the lower tropospheric level and prevailing synoptic condition over the region. The second peak is mainly controlled by the moisture content in the air and the orography of the area. The differences in the values for rain yield in the premonsoon and monsoon seasons may be due to the differences in the cloud microphysical and electrical properties. There is good parallelism in the variation of flash rate density and CAPE. The correlation coefficient between these two parameters is 0.90 which is highly significant at <0.0001 %.